Breaking Bad News to a Prospective Cross-Sectional Sample of Patients’ Relatives in a Nigerian Neurosurgical Service - Adeleye, Amos O.; Fatiregun, Akinola A. (Frontiers in Neurology, 2013)
Objectives: Breaking of medical bad news is anecdotally deemed culturally unacceptable, even intolerable, to native Africans. We explored this hypothesis among a cohort of relatives of patients who had difficult neurosurgical diagnoses in an indigenous practice. Materials and Methods: A semi-structured, interviewer-administered questionnaire was used in a cross-sectional survey among a consecutive cohort of surrogates / relatives of concerned patients. Their opinion and preferences regarding the full disclosure of the grave neurosurgical diagnoses, and prognoses, of their wards were analysed. Results: A total of 114 patients’ relatives, 83 (72.8%) females, were sampled. They were mainly young adults, mean age 40.2(SD 14.2) years; 57% had only basic literacy education; but the majority, 97%, declared themselves to have serious religious commitments. Ninety nine percent of the study participants deemed it desirable that either they or the patients concerned be told the bad news; 80.7% felt that this is best done with both patients and relations in attendance; 3.5% felt only the patients need be told. These preferences are similar to those expressed by the patients themselves in an earlier study. But a nearly significant greater proportion of patients’ relatives (15 vs 5%, p=0.06) would rather be the only ones to be told the patients’ bad news. Conclusions: This data-driven study showed that contrary to anecdotal belief about them, a cohort of native Nigerian-African surrogates of neurosurgical patients was well disposed to receiving, and appeared able to handle well, the full disclosure of difficult medical diagnostic / prognostic information.